Strength asymmetry of the shoulders in elite volleyball players - Hadzic, V.; Sattler, T.; Veselko, M.; Markovic, G.; Dervisevic, E. (Journal of Athletic Training, 2014)
Context: Volleyball players are reported to have shoulder strength imbalances. Previous authors have primarily investigated small samples of male players at a single skill level, without considering playing position, and with inconsistent findings.